2012
DOI: 10.1017/s0950268812002142
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities on food court tables and cleaning equipment in a shopping mall

Abstract: The food court at a shopping mall is a potential transfer point for pathogenic microbes, but to date, this environment has not been the subject of detailed molecular microbiological study. We used a combination of culture-based and culture-independent approaches to investigate the types and numbers of bacteria present on food court tables, and on a food court cleaning cloth. Bacteria were found at 10²-10⁵ c.f.u./m² on food court tables and 10¹⁰ c.f.u./m² on the cleaning cloth. Tag-pyrosequencing of amplified 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…On the other hand, a study conducted in Australia reported that bacteria were found at 10 2 -10 5 CFU/m 2 (max. 10 CFU/cm 2 ) on food court tables in a shopping mall, which is a much lower result than that conveyed by the present study [17] In a further study, the number of heterotrophic bacteria on shopping cart handles ranged between 6 and 133 CFU/cm 2 [18], which is comparable to the present study that reported around 20.8 CFU/cm 2 on shopping cart handles (520 CFU/25 cm 2 ).…”
Section: Resultscontrasting
confidence: 56%
“…On the other hand, a study conducted in Australia reported that bacteria were found at 10 2 -10 5 CFU/m 2 (max. 10 CFU/cm 2 ) on food court tables in a shopping mall, which is a much lower result than that conveyed by the present study [17] In a further study, the number of heterotrophic bacteria on shopping cart handles ranged between 6 and 133 CFU/cm 2 [18], which is comparable to the present study that reported around 20.8 CFU/cm 2 on shopping cart handles (520 CFU/25 cm 2 ).…”
Section: Resultscontrasting
confidence: 56%
“…These results may be affected by the common usage of wooden furniture and the cleaning method used by the schools which likely cause floor dirt to be suspended and settle on desks. The fact that students did not have a cafeteria but ate at their desks could influence the microbial contamination of the desks by bacteria that feeds on crumbs …”
Section: Discussionmentioning
confidence: 99%
“…The fact that students did not have a cafeteria but ate at their desks could influence the microbial contamination of the desks by bacteria that feeds on crumbs. 87 The sample size of five schools studied in this work may be the main limiting factor affecting the assessment of IEQ in Nigerian elementary schools. Another factor may be the period of sampling during the dry season which did not cover the entire season range in Nigeria, the rainy season being associated with cooler temperature as compared to the dry season.…”
Section: Discussionmentioning
confidence: 99%
“…; Huys et al . ; Dingsdag and Colman ). Other bacteria such as spore‐forming and nonpathogenic Paenibacillus sp, and Flavobacterium sp.…”
Section: Resultsmentioning
confidence: 99%